In vivo bone regeneration performance of hydroxypropyl methylcellulose hydrogel-based composite bone cements in ovariectomized and ovary-intact rats: a preliminary investigation - Mosharraf Hossain; Tamima Sultana; Ji Eun Moon; Soobin Im; Je Hoon Jeong (Journal of Materials Science: Materials in Medicine)
Abstract The objective of this study is to fabricate and develop hydroxypropyl methylcellulose (HPMC) hydrogel (HG)-based composite bone cements with incorporation of hydroxyapatite (HA), beta-tricalcium phosphate (β-TCP), and with/without polymethylmethacrylate (PMMA) for vertebroplasty. For animal study, twenty female Wister rats (250–300 g, 12 weeks of age) were divided into four groups including a two non-ovariectomy (NOVX) groups and two ovariectomy (OVX)-induced osteoporosis groups. Two prepared biocomposites including HG/β-TCP/HA and HG/β-TCP/HA/PMMA were injected into the tibial defects of both OVX and NOVX rats for evaluating in vivo osteogenesis after 12 weeks. Micro-computed tomography and histological analysis using hematoxylin and eosin (H&E) and Masson's trichrome stains of the two composite cements implanted into the tibial defects of OVX and NOVX rats revealed enhanced bone regeneration potential. However, no statistically significant differences were noted among the groups based on new bone formation, demonstrating that the injected composite cements showed similar osteogenesis effects in both OVX and NOVX rats. These findings suggest that the newly developed composite bone cement composed of HG, β-TCP, HA and/or PMMA may be a promising and professional tool for treating osteoporotic and non-osteoporotic vertebral fractures.